Modified Chitosan-Clay Nanocomposite as a Drug Delivery System Intercalation and In Vitro Release of Ibuprofen. (23rd October 2013) - Abdeen, Rehab; Salahuddin, Nehal
Abstract : The present paper focused on the intercalation of ibuprofen into sodium montmorillonite, chitosan, and chitosan montmorillonite nanocomposites as a sustained release drug carrier. The compounds were characterized by X-ray diffraction (XRD), infrared spectroscopy (IR), thermogravimetric analysis (TGA), and transmission electron microscopy (TEM). The basal spacing of montmorillonite increased from 9.6 Å to 19.6 Å indicating the intercalation of modified chitosan and ibuprofen between lamellar layers. UV spectroscopy was employed to monitor the in vitro drug release processes in both pH 5.4 and 7.8 solutions. The results revealed that ibuprofen was released from MMT, CS, and Mod-CS/MMT steadily and was pH dependent.